Primary Prevention of Cancer-Associated Thrombosis: Current Perspectives - Hart, Christina; van Es, Nick; Voigtlaender, Minna (Hämostaseologie, 2024)
Over the past two decades, the incidence of cancer-associated thrombosis (CAT) has increased. It is nowadays a common and often serious complication among patients with cancer. Although medical thromboprophylaxis is recommended for most surgical and nonsurgical cancer patients, it has been infrequently used in ambulatory patients with cancer because of the burden of treatment and concerns about bleeding. However, various risk assessment scores are now available and randomized placebo-controlled trials have established the efficacy of low-molecular-weight heparin or the direct oral Xa inhibitors rivaroxaban and apixaban in ambulatory patients with cancer at high risk of venous thromboembolism (VTE). This review provides an overview of (1) primary thromboprophylaxis in the setting of hospitalized surgical and medical patients, (2) extended thromboprophylaxis after hospital discharge, (3) performance of risk assessment tools for CAT, and (4) primary thromboprophylaxis in ambulatory patients with cancer. The aim is to provide support to physicians in identifying ambulatory patients with cancer at high VTE risk who benefit most from medical thromboprophylaxis according to current recommendations from international guidelines.
Keywords: cancer; thrombosis; prophylaxis; ambulatory patients; anticoagulants